Optimization of banana commodities in sipora jaya village based on home industry as a banana production Center in West Sumatera - Aura Zahra Nafisah; Welli Andriani; Muhammad Zikri Arifin; Ramos Mardiansyah; Dhio Ervandi; Siska Alicia Farma (Penerbit Universiti Kebangsaan Malaysia, 2024)
Home industry or household industry is a business unit that is not in the form of a legal entity and is carried out by several household members, with the activity of changing basic materials into finished or semi-finished goods with the aim of selling. The aim of this activity is to optimize the banana commodity in Sipora Jaya village based on a home industry as a banana production center in West Sumatra. The method used in this research is the community empowerment method using the participation method. The community will participate and be directly involved with students in the program implementation process. In this program, assistance will be provided in the processing of processed banana products from upstream to downstream which is divided into three subsystems, namely; (1) Product processing subsystem, which processes bananas into three processed derivative products with selling value; (2) Packaging and marketing subsystem, which consists of assistance in product packaging and marketing; (3) Institutional strengthening subsystem, to strengthen the institutional management of the PKK group. In this program, the fostered partners are 10 PKK women from Sipora Jaya village. So the result can be obtained that tcount is greater than ttable, namely 14.548> 1.83311 and Sig. (2 tailed) = 0.000 < 0.05, then Ho is rejected and Ha is accepted. So it can be concluded that there is an influence between training and guidance on optimizing banana commodities based on the banana home industry on increasing knowledge in diversifying processed banana products with selling value.